RELATIONSHIP OF URINARY C-TERMINAL TELOPEPTIDE COLLAGEN TYPE-II (CTX-II) LEVEL WITH THE DEGREE OF JOINT DAMAGE IN PATIENTS WITH KNEE OSTEOARTHITIS - Handono, Kusworini; **, Farida; Suryana, BP Putra; Listyawati, Enny (Medicina, 2012)
Radiography of the knee is used to confirm the diagnosis and classification of knee OA severity. Urinary CTX- II  is a biochemical marker for assessing cartilage degradation of knee OA. This research aimed to analyze the correlation between the level of urinary CTX-II  and the radiographic severity of knee OA. Research was conducted in 40 patients with knee OA ( ACR criteria ) and 40 age and sex matched healthy controls. Wheight bearing anteroposterior and lateral semiflexed radiographs were taken of both knee. The patients were stratified based on the Kellgreen-Lawrence (K-L) score. Urinary CTX-II level was measured using ELISA competitive method. Correlation between urinary CTX-II level and radiographic knee OA severity was analyzed with Spearman Correlation. Statistical significance level at P < 0.05. Mean urinary CTX-II level was significantly higher in patients with OA compared with healthy controls (447.7( SB 316.39) ng/ml vs 289(SB 168.01) ng/mmol respectively, P = 0.023). There was a significant difference between urinary CTX-II level in patients with  grade ? 2 K-L knee OA compared with patients with grade > 2 K-L (240.35 (SB 88.90) ng/mmol vs 728.24 (SB 295.15) ng/mmol respectively; P < 0.001). The urinary CTX-II level was significantly associated with the degree of joint lesion in patients with OA (r = 0.734; P = 0.0001). Urinary level of CTX-II is strongly associated with the degree of radiographic joint lesion of OA